RANCANGAN SUMUR RESAPAN UNTUK KONSERVASI MATA AIR DI DESA DLINGO, KECAMATAN MOJOSONGO, KABUPATEN BOYOLALI - Muhammad Ario Baskoro; Yogafanny, Ekha; Widiarti, Ika Wahyuning (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2022)
The need of clean water continues to increase as the population increases. This shows that it is necessary to take conservation actions and resource management actions so the water source existence and capabilities can be maintained properly. This study aims to determine the design of infiltration wells that can be applied to maintain the spring quantity and sustainability that exists in Dlingo Village, Mojosongo District, Boyolali Regency so that they are available to meet domestic needs, both at the present and in the future. The methods that used in this research are including mathematical methods, descriptive analysis methods, and spatial analysis methods. This research was carried out through several activities including surveis, topographic and slope mapping, groundwater flow direction mapping, rainfall measurement, runoff discharge calculation, and making the design of infiltration well. Based on the calculation results, it is necessary to install infiltration wells with a volume of 2.2608 m3 with total of 150 wells in the study area. It is estimated that the presence of these infiltration wells can increase water infiltration by 0.33912 m3 when the rain comes.